Intravascular Optical-Resolution Photoacoustic Tomography with a 1.1 mm Diameter Catheter - Bai, Xiaosong (Public Library of Science, 2014)
Photoacoustic imaging is an emerging technology that can provide anatomic, functional, and molecular information about biological tissue. Intravascular spectroscopic and molecular photoacoustic imaging can potentially improve the identification of atherosclerotic plaque composition, the detection of inflammation, and ultimately the risk stratification of atherosclerosis. In this study, a first-of-its-kind intravascular optical-resolution photoacoustic tomography (OR-PAT) system with a 1.1 mm diameter catheter is developed, offering optical-diffraction limited transverse resolution as fine as 19.6 μm, ∼10-fold finer than that of conventional intravascular photoacoustic and ultrasonic imaging. To offer complementary imaging information and depth, the system also acquires co-registered intravascular ultrasound images in parallel. Imaging of an iliac stent and a lipid phantom shows that the high resolution and contrast of OR-PAT can enable improved stent implantation guidance and lipid identification. In the future, these capabilities may ultimately improve the diagnosis and interventional treatment of vulnerable atherosclerotic plaques, which are prone to cause thrombotic complications such as myocardial infarction and stroke.